Factors Influencing the Use of Vct (Voluntary Counseling & Testing) Clinics In Groupsmsm (Male Sexual Men) at Kendari City Hospital - Indraswary, Metha; Munir, Sanihu; Noviyanti Rahcman, Wa Ode Nova (Magister Kesehatan Universitas Mandala Waluya, 2025)
Introduction: The VCT Clinic service program is an early detection effort to determine whether a person has been infected with HIV or not through Voluntary Counseling and Testing. Risky sexual behavior with HIV/AIDS is among the MSM group. The aim of this research is to determine the factors that influence the utilization of VCT services in the MSM group. Method: This research is a type of quantitative research with an approach using a cross-sectional study design. The population in this study is all families (heads of families). The population in this study is all HIV/AIDS sufferers who are undergoing ARV treatment at the Kendari City Hospital in 2023, namely 349 people. Result: The results found that 26.3% of the MSM group did not utilize the VCT clinic at, while 73.7% of the MSM group made good use of the VCT clinic. 69.7%. The attitude of the MSM group was negative towards VCT clinics as much as 25% and 75% of the MSM group had a positive attitude towards VCT clinics. The MSM group with negative actions was 28.9% and 71.1% of the MSM group with positive actions. The MSM group who received less family support to utilize the VCT clinic was 34.2%, while 65.8% of other respondents received good family support to utilize the VCT clinic. Conclusion: The results of the analysis show a significance value of <0.05, meaning that there is an influence of knowledge, attitudes, actions, social support and family support on the use of VCT clinic services.